Analisis Kinerja Sistem Penggilingan Gabah Sebagai Penunjang Usaha Pertanian Berkelanjutan (Studi Kasus di Kecamatan Penebel, Kabupaten Tabanan) - Ni Made Ayu Manik Suantari; IG.N.Apriadi Aviantara; I.A.Rina PratiwiPudja (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2018)
The purpose of this study is to determine the performance of grain milling machines and the percentage of capacity used, in order to assess the financial sustainability of the grain milling business. Financial sustainability was analyzed using NPV (Net Present Value), IRR (Internal Rate of Return), and BCR (Benefit Cost Ratio). NPV indicates the difference between cash generated by the investment and the required investment value. IRR shows whether an investment is feasible compared to alternative rates of return. BCR evaluates the comparison between the value of benefits and costs at present value. The analysis of operational performance showed that small-capacity mills contributed 21.1%, medium-capacity mills 32.3%, and large-capacity mills 47.5% to overall performance. Large-capacity mills had the highest contribution to operational performance and were considered the most viable for continued operation, while small-capacity mills were deemed less appropriate for continuation. Financial feasibility analysis indicated that NPV values were Rp. 306,400,273 for large capacity, Rp. 190,596,835 for medium capacity, and Rp. -15,890,115 for small capacity. IRR values were 48% for large, 24% for medium, and 0.6% for small capacity. BCR values were 2.18 for large, 1.75 for medium, and 1.0 for small capacity.